Investigation of the Catalytic Degradation of Dotriacontane over the Diluted Forms of Modenite, Ultra Stable Zeolite Y and ZSM-5 in Fluidized Bed Reator - R. Zaggout, Farid (Asian Journal of Chemistry, 2010)
Dotriacontane was degraded over the diluted forms of zeolites (ZSM-5), ultrastable zeolite Y(USY) and mordenite (MORD) using laboratory fluidized bed reactor (FBR) operating at 360°C. The degradation of dotriacontane resulted in the production of gaseous hydrocarbons vaying in the range of C1-C8. Experiments carried out with the diluted forms of zeolites gave good yields of,volatile hydrocarbon with different selectivities in the final products depending on the type of zeolite used in the degradation.